Influences of argatroban on five fibrinogen assays - Zhang, L.; Yang, J.; Zheng, X.; Fan, Q.; Zhang, Z. (International journal of laboratory hematology, 2017)
Introduction Argatroban, as a direct thrombin inhibitor, prolongs the clotting time. However, detection of clotting time is the base of routine fibrinogen assays, including Clauss method and derived method. The influences of argatroban on fibrinogen assays are still unclear. Methods Normal pooled plasma (NPP) from 20 healthy subjects was spiked with increasing argatroban concentrations (0‐3.2 μg/mL). Then the NPP samples were analyzed by five fibrinogen assays: HemosIL Fibrinogen‐C XL reagent (Clauss method) on ACL‐TOP; STA‐Fibrinogen reagent (Clauss method) on STA‐R Evolution; Siemens Thrombin reagent (Clauss method) on CS‐5100; SynthASil RecombiPlasTin 2G reagent (PT‐derived method) on ACL‐TOP; and N Antiserum to Human Fibrinogen reagent (NAHF, Immunoassay) on BN2 nephelometer analyzer. Results Argatroban had no influences on NAHF (P=.13). Compared with the NAHF, significant reduction was observed on Fibrinogen‐C XL (P<.01), while no influences were shown on the others (STA‐Fibrinogen: P=.41, Siemens Thrombin: P=.20, RecombiPlasTin 2G: P=.21) when activated partial thromboplastin time (APTT) ratio was no more than 3.0. As APTT ratio was increasing to 4.5, results from Clauss and PT‐derived methods were significantly lowered (STA‐Fibrinogen: P=.02, Siemens Thrombin: P<.01, Fibrinogen‐C XL: P<.01, RecombiPlasTin 2G: P<.01). Conclusion The influences of argatroban on fibrinogen assays differ greatly, clinicians should be aware of the influences of argatroban on the fibrinogen assays used on site to avoid misdiagnoses.